Assistência técnica na agricultura brasileira: Uma análise sobre a origem da orientaç\~ao técnica por meio do Censo Agropecuário de 2017 - Caroline Nascimento Pereira; César Nunes De Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Technical assistance as a support tool and source of information for rural producers has undergone several transformations over the years. After brief attempts to introduce the service, ATER gained strength in the period of agricultural technification in the 1960s. Agricultural credit provided resources for producers to introduce the technological package to crops, which was disseminated through technical assistance among agricultural establishments. Some decades passed after the creation, and even dismantling, of the main institutions and entities in the sector, but technical assistance remains an indispensable service to improve the performance of the productive activity, in addition to the possibility of reducing costs and increasing profitability. Furthermore, the role of extension workers is essential to collaborate with social issues in the field, such as productive organization, associations, among others. Despite the proven importance, only 20% of Brazilian agricultural establishments have some type of technical guidance in the 2017 Agricultural Census. The public ATER, which has great capillarity throughout Brazil and qualified human capital, showed a reduction in performance among the 2006 Agricultural Census and 2017. In opposite, other sources of technical guidance have shown significant growth, such as self-orientation and cooperatives. The greater use of other sources is welcome, mainly due to the specificities of each region and the type of agriculture practiced, however many establishments, mainly in the North and Northeast of Brazil, do not have the resources and scale to hire their own employees or in the region there is no culture cooperatives, which prevents the production of many small establishments.
Keywords: Q1; Q16; 330; Ater; cooperatives; integrating companies; System S.